1992
DOI: 10.1063/1.107783
|View full text |Cite
|
Sign up to set email alerts
|

High-power strained-layer InGaAs/AlGaAs tapered traveling wave amplifier

Abstract: Articles you may be interested inFacet temperature reduction by a current blocking layer at the front facets of high-power InGaAs/AlGaAs lasers J. Appl. Phys. 93, 1848 (2003); 10.1063/1.1531839 High-power continuous-wave operation of a InGaAs/AlGaAs quantum dot laser J. Appl. Phys. 83, 5561 (1998); 10.1063/1.367390 Highpower operation of strained InGaAs/AlGaAs single quantum well lasers Appl. Phys. Lett. 59, 2642 (1991); 10.1063/1.105924 Highpower conversion efficiency in a strained InGaAs/AlGaAs quantum well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…However, broad-area MOPA devices possess inherent instabilities due to refractive index variations induced by thermal gradients and injected carriers [6]-[SI. The position of external spherical lenses required to achieve diffraction-limited, collimated beams is drive dependent [2]- [4]. These facts may explain why there have been no reliability data available for MOPA devices after more than three years from commercial introduction.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…However, broad-area MOPA devices possess inherent instabilities due to refractive index variations induced by thermal gradients and injected carriers [6]-[SI. The position of external spherical lenses required to achieve diffraction-limited, collimated beams is drive dependent [2]- [4]. These facts may explain why there have been no reliability data available for MOPA devices after more than three years from commercial introduction.…”
mentioning
confidence: 96%
“…However, single-stripe, large-aperture lasers are inherently multimodal since the number of lateral modes within a single stripe increases with aperture width. Recently, fanouttype master-oscillator power-amplifier (MOPA) devices of the "broad-area'' type have displayed watts of diffractionlimited, single-frequency power [2]-[SI. However, broad-area MOPA devices possess inherent instabilities due to refractive index variations induced by thermal gradients and injected carriers [6]-[SI.…”
mentioning
confidence: 99%
“…The beam quality in the conventional tapered lasers can be improved by using beamspoilers at the RW/taper junction [11] to reflect away the backward propagating beams into the lossy, unpumped regions of the material. The effect of using a beamspoiler in a conventional tapered laser was investigated and compared against the performance of the DBR tapered laser (without a beamspoiler).…”
Section: Use Of a Beamspoiler In The Conventional Tapered Laser Diodesmentioning
confidence: 99%
“…The influence of the front facet reflectivity and the taper angle on the beam quality is considered in Section 5. The improvements obtained by using a beamspoiler in the conventional lasers [11] is then discussed and compared with the performance of a standard DBR laser.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating pseudomorphic In x Ga 1-x As quantum wells in an Al y Ga 1-y As-GaAs material system has resulted in a structure which allows for an increased band filling and tuning range extending to 130 nm [30] (845.4 nm < l < 975.6 nm). However, broadly tunable QW laser diodes have been mainly focused on materials which contain multiple identical wells (MQW) [33,26] including QWs with strained layers [34]. In addition, gain calculations and experiments have shown that a wider and flatter gain profile than that of a material which consists of say three identical QWs can be obtained when we use non-identical QWs [35] with different QW width or barrier height.…”
Section: Semiconductor Optical Amplifiersmentioning
confidence: 99%